1994
DOI: 10.1002/app.1994.070521204
|View full text |Cite
|
Sign up to set email alerts
|

Effects of reactive functional groups in the compatibilizer on mechanical properties of compatibilized blends

Abstract: SYNOPSISThe compatibility of blends of polyamide-6/ [styrene-(ethylene-butylene) -styrene] triblock copolymer (SEBS) was enhanced with a compatibilizer, maleated SEBS, whose compositions were varied from 0 to 4 wt % of the blends. The maleated SEBS ( MA-g-SEBS) was synthesized by reacting (grafting) maleic anhydride (MA) with SEBS in the laboratory at various maleic anhydride concentrations ranging from 8 to 13 wt % of the maleated compatibilizer. The effects of graft levels of the reactive MA functional group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
2

Year Published

1995
1995
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 11 publications
1
13
0
2
Order By: Relevance
“…The decrease in the rubber particle size observed up to 1.0% epoxy content agreed with the higher interactions at the interface expected as a consequence of the observed grafting reactions 9, 20, 21, 26, 27, 56, 57. This is because larger epoxy contents should lead to an increase in the number of functional groups, leading to a higher probability of interaction.…”
Section: Resultssupporting
confidence: 81%
“…The decrease in the rubber particle size observed up to 1.0% epoxy content agreed with the higher interactions at the interface expected as a consequence of the observed grafting reactions 9, 20, 21, 26, 27, 56, 57. This is because larger epoxy contents should lead to an increase in the number of functional groups, leading to a higher probability of interaction.…”
Section: Resultssupporting
confidence: 81%
“…[6]. However, both in the case of SEBS and LLDPE/PS mixture, having the same composition as SEBS, only the aliphatic radical appears to take part in the grafting reaction.…”
Section: Discussionmentioning
confidence: 98%
“…Many reports are devoted to the study of the properties of polyamide/functionalized-SEBS blends [4][5][6][7][8] and in general an increase of mechanical properties is observed when SEBS-g-MAH as compatibilizer was used. This grafted copolymer seems to be a better compatibilizer than a similarly functionalized polyolefin such as EPR-g-MAH.…”
Section: Introductionmentioning
confidence: 99%
“…The final properties of these blends are strongly affected by the volume fraction of the components, the size and shape of domains, and the interfacial tension and adhesion between the two phases. Many publications [1][2][3][4][5][6][7] reported that the presence of a block or graft copolymer, which has similar structure or can react chemically with the blending components, could provide lowering of the interfacial energy, improvement of the interfacial adhesion between the two phases, and reduction of the size of dispersed particles in the blends.…”
Section: Introductionmentioning
confidence: 99%